2000
DOI: 10.1093/bja/85.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of intravenous fluid preload before epidural analgesia during labour

Abstract: We performed a randomized controlled trial of the effect of intravenous fluid preload on maternal hypotension and fetal heart rate (FHR) changes in labour after the first epidural injection. Group 1 (49 women) received 1 litre of crystalloid preload. Group 2 (46 women) received no preload. No statistically significant difference was shown between the two groups for either of the outcomes. Hypotension was found in three women in group 1 and five in group 2 (P = 0.4). Deterioration in FHR pattern was found in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…Intravenous fluids are commonly given in the routine management of patients undergoing major surgery to replace losses and maintain normal circulating blood volume [83]. Abnormalities in the capacity to manage fluid in the perioperative setting, however, along with erroneous estimates of insensible, evaporative or third space losses can contribute to excessive fluid therapy and lead to complications and adverse outcomes [84,85].…”
Section: Fluid Therapy In Major Surgerymentioning
confidence: 99%
“…Intravenous fluids are commonly given in the routine management of patients undergoing major surgery to replace losses and maintain normal circulating blood volume [83]. Abnormalities in the capacity to manage fluid in the perioperative setting, however, along with erroneous estimates of insensible, evaporative or third space losses can contribute to excessive fluid therapy and lead to complications and adverse outcomes [84,85].…”
Section: Fluid Therapy In Major Surgerymentioning
confidence: 99%
“…19 The resulting hypotension is commonly treated with additional intravenous volume and vasopressor administration. 20-23 Prophylactic intravenous volume and/or vasopressor administration is commonly used prior to regional anesthesia to minimize the occurrence of hypotension. 16,22,24 In our previously published studies, we have observed that Class III obese women (Body Mass Index, BMI ≥40 kg/m 2 ) undergoing regional anesthesia for childbirth have more anesthesia-related hypotension and fetal heart rate abnormalities than lean gravidas.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Prehydration or preloading is commonly administered but it has controversial results. [7,8] Despite all conservative measures, a vasopressor drug is oft en required to prevent hypotension during spinal anesthesia. [13] In this study, all patients in the two groups were comparable with respect to age and ASA status.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Prehydration or preloading is commonly administered but it has controversial results. [7,8] Because of the poor effi cacy of nonpharmacological techniques to eff ectively manage hypotension, a vasopressor is usually required during spinal anesthesia for cesarean section. In choosing an appropriate vasopressor in obstetrics, a number of factors like efficacy for maintaining blood pressure, noncardiovascular maternal eff ects, ease of use, direct and indirect fetal eff ects, cost, and availability need to be considered.…”
Section: Introductionmentioning
confidence: 99%